Influencia táctica del resultado parcial en los saques de esquina en fútbol - Casal, C. A.; Losada, J. L.; Maneiro, R.; Arda, T. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2017)
The aim of this study was to examine the effects of the situational variable match status on corner kicks performance indicators in 95 matches played during the final stages of the 2012 UEFA European Championships and the 2010 FIFA World Cup. Video recordings of the matches were analyzed and coded post-event using notational analysis. Multiple interactions between the performance indicators and match status were analyzed using the Chi-squared automatic interaction detection (CHAID) decision-tree method. The results show that when a corner kick is taken during the last 30 minutes of the match, teams that are losing place 6 or more attackers in the shooting area, while teams that are drawing place 2-5 attackers in this area. In the same situation, teams that are drawing place 1-2 defenders at the goalposts while winning teams place none.